Winner will give prize to college: alum donating rich reward to Davidson - Henderson, Bruce, author; Charlotte Observer, publisher (Colorado State University. Libraries, 2003)
As a student at Davidson College fifty years ago Holmes Rolston discovered a world of wonder at the end of a microscope. As a winner of the world's best-known religion prize he's ready to repay the favor. He has donated the prize to establish a chair of science and religion, the disciplines he has worked a lifetime to link.
Keywords: philosophy professor; Colorado State University; Davidson College; Templeton Prize; Rolston, Holmes, 1932-2025